Moderasi Reward Pada Pengaruh Sistem Akuntansi Manajemen Dan Pengukuran Kinerja Terhadap Kinerja Manajerial (Studi Kasus Perusahaan Bumn Di Kota Medan) - Fadillah Anwar; Edisah Putra Nainggolan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the relationship between Managerial Performance (Y) and the Influence of Rewards (X1), Management Accounting Systems (X2), and Performance Measurement (X3). The research method used is descriptive quantitative. The Likert scale is used to assess factors and methods of collecting data through surveys. A total of 30 BUMN companies in Medan City were sampled for the population of BUMN companies in the city in this study. Partial Least Square-Structural Equation Modeling (PLS-SEM), which was performed using SmartPLS version 3.0 software, is the data analysis method used in this study. The research findings show that the reward variable partially has a positive and significant effect on managerial performance. The management accounting system variable partially has a positive and significant effect on managerial performance. The performance measurement variable partially has a negative and insignificant effect on managerial performance. Keywords: Reward, Management Accounting System, Performance Measurement and Managerial Performance